The Preparation of Stereoisomeric Tricyclo[4.2.1.02,5]nona-7-ene-3,4-dicarboximides and Anhydrides: Literature Corrections and New Products - Kearns, Philip S.; Wells, Bryant K.; Warrener, Ronald N.; Margetić, Davor (Synlett, 2014)
The bis-homo Diels–Alder reactions of maleimide and N-methylmaleimide with quadricyclane are shown to produce mixtures containing both the exo,anti- and exo,syn-tricyclo-[4.2.1.02,5]nona-7-ene-3,4-dicarboximides, whereas the isomeric endo,anti-adducts are available from the reaction of cyclopentadiene with the appropriate cyclobutene-3,4-dicarboximides. The related reaction of quadricyclane with maleic anhydride had been erroneously reported to form single adducts; our work shows that two stereoisomers are actually formed and these have been chemically related to the maleimide and N-methylmaleimide adducts. The proton chemical shifts of the adduct formed by reaction of cyclobutene-3,4-dicarboxylic anhydride with cyclopentadiene have also been miss-assigned. Preparation of [3] and [5] polynorbornane scaffolds with terminal succinimides have been effected by coupling the stereoisomeric adducts at the norbornene π-bond by using 2,5-bis(trifluoromethyl)-1,3,4-oxadiazole and bisepoxide. The spacer shapes and dimensions have been determined by molecular modelling.
Keywords: cycloaddition; Diels–Alder reaction; quadricyclane; norbornenes; stereochemistry